THE CONSISTENCE OF A SERIES OF TERMS IN THE ROMANIAN LAW CONCERNING CONSUMPTION REGULATION - Voiculescu, Ion Cătălin (Journal of Advanced Research in Law and Economics, 2017)
Given that approximately 70% of Romanian households’ incomes are targeted to consumption, establishing a sTable and coherent legal regime for the rights of what we call the consumer is extremely important. What is the consumer and the professional is not a question easy to answer, considering the use of these concepts in various acts and especially with changing acquis Romanian consumer rights are included as a principle in the Consumer Code and are detailed in various vertical sectors, through various regulations. It is therefore necessary to create horizontal tools to unify these prerogatives.
Keywords: consumer, professional, consumer protection, consumer rights